Dendritic cells and pluripotency: unlikely allies in the pursuit of immunotherapy. (May 2015) - Fairchild, Paul J; Leishman, Alison; Sachamitr, Patty; Telfer, Caroline; Hackett, Simon; Davies, Timothy J
As the fulcrum on which the balance between the opposing forces of tolerance and immunity has been shown to pivot, dendritic cells (DC) hold significant promise for immune intervention in a variety of disease states. Here we discuss how the directed differentiation of human pluripotent stem cells may address many of the current obstacles to the use of monocyte-derived DC in immunotherapy, providing a novel source of previously inaccessible DC subsets and opportunities for their scale-up, quality control and genetic modification. Indeed, given that it is the immunological legacy DC leave behind that is of therapeutic value, rather than their persistence per se, we propose that immunotherapy should serve as an early target for the clinical application of pluripotent stem cells.